Preadipocyte-induced upregulation of IGFBP5 enhances ovarian cancer tumorigenesis via CREB signaling - Jennifer A. Waters; Cassidy Lucht; Sofia Howe; Gregory J. Jordan; Ixchel Urbano; Samuel F. Gilbert; Richard M. Cripps; Mikella Robinson; Carrie D. House (iScience)
Summary: Dissemination of ovarian cancer cells during metastasis is heavily influenced by omental cells from the adipose tumor microenvironment. We previously found that omental adipocyte precursors, or preadipocytes, promote stress tolerance and tumorigenesis of ovarian cancer cells and this was correlated with upregulation of insulin-like growth factor-binding protein 5 (IGFBP5). Here, we tested whether IGFBP5 mediates stress tolerance and tumorigenesis. Using in vitro and in vivo knockdown and overexpression models we found that IGFBP5 drives tumor-initiating cell phenotypes with increased adhesion, clonogenic potential, stress tolerance, and tumor initiation. Reciprocally, knocking down IGFBP5 reduced these features. Mechanistically, we found that preadipocyte-secreted factors increase expression of IGFBP5 in cancer cells which activates CREB to enhance cell survival. Targeting CREB using a pharmacological inhibitor reversed the IGFBP5 induced phenotypes. These findings further support the role of preadipocytes in ovarian cancer progression and suggest therapeutically targeting IGFBP5 or CREB may reduce ovarian cancer metastasis.